An overview of the relationship between anaemia, iron, and venous leg ulcers. Issue 6 (16th August 2019) - Ferris, Amy E.; Harding, Keith G.
Abstract: The factors preventing healing in venous leg ulcers are still not fully understood. Iron‐mediated tissue damage has been hypothesised, yet anecdotally anaemia is also thought to have a negative effect on wound healing. This article summarises the current evidence for these theories and their likely effects in the context of venous ulceration. A comprehensive search of the literature was conducted. Studies suggest that a number of forms of iron including haemosiderin and ferritin are implicated in progression of venous disease, ulcer formation, and impaired healing, which is thought to be primarily free radical mediated. There is a paucity of evidence for the role of iron deficiency and anaemia on ulcer healing; however, there is likely to be a highly complex interplay between the damaging effects of iron on local tissues and the negative effects of anaemia‐mediated tissue hypoxia. Studies looking at options to increase local oxygen delivery such as topical haemoglobin suggest that this may have an impact on some aspects of healing, but findings are generally inconclusive. There is growing evidence that locally elevated iron levels may have a detrimental effect on ulcer healing and formation; however, more robust research is needed.